The IGF-I/cortisol ratio as a useful marker for monitoring training in young boxers - S Nassib; W Moalla; S Hammoudi-Nassib; M Chtara; Y Hachana; Z Tabka; K Chamari; M Elloumi (Termedia Publishing House, 2016)
Training effects on plasma insulin-like growth factor-1 (IGF-1)/cortisol ratio were investigated in boxers. Thirty subjects were assigned to either the training or the control group (n=15 in both). They were tested before the beginning of training (TO), after 5 weeks of intensive training (T1), and after 1 week of tapering (T2). Physical performances (Yo-Yo intermittent recovery test level-1), training loads, and blood sampling were obtained at T0, T1, and T2. Controls were only tested for biochemical and anthropometric parameters at T0 and T2. A significantly higher physical performance was observed at T2 compared to T1. At T1, cortisol levels were significantly increased whereas IGF-1 and insulin-like growth factor binding protein-3 (IGFBP-3) levels remained unchanged compared to baseline. At T2, cortisol levels decreased while IGF-1 and IGFBP-3 levels increased. The IGF-1/cortisol ratio decreased significantly at T1 and increased at T2, and its variations were significantly correlated with changes in training loads and Yo-Yo intermittent recovery test level 1 (IRT1) performance over the training period. Cortisol variations correlated with changes in training load (r=0.64; p<0.01) and Yo-Yo IRT1 performance (r=O.78; p<0.001) at T1 whereas IGF-1 variations correlated only with changes in Yo-Yo IRT1 performance at T2 (r=0.71; p<0.001l. It is concluded that IGF-1/cortisol ratio could be a useful tool for monitoring training loads in young trained boxers.